A novel protection scheme for low voltage DC microgrid using inductance estimation. (September 2020) - Shamsoddini, Morteza; Vahidi, Behrooz; Razani, Ramin; Mohamed, Yasser Abdel-Rady I.
Highlights: A new protection scheme based on local measurement for LVDC microgrids is proposed. Fault current equation is used to estimate equivalent inductance of fault path. This scheme is faster than existing methods, and Backup protection is provided in this scheme. The proposed protection scheme is adaptive against any changes in the microgrid. Superiority of the proposed scheme is verified through various case studies. Abstract: Vulnerability of power electronic converters in DC microgrids when pole to ground and pole to pole fault occur necessitates using an effective fault detection and isolation. Most of the proposed fault detection methods use a communication system to exchange data among protection units, which could be an Achilles heel for the entire protection scheme. In this paper, fault detection based on estimation of equivalent inductance using simplified fault current equation is proposed. In the presented method, only local measurement is required and communication system is avoided due to reliability issues. In order to improve equivalent inductance estimation, an artificial line inductance (ALI) is implemented at both ends of each line. Since estimated equivalent inductance only depends on protection zone inductances including line inductance and ALIs, any change in topology of the microgrid does not affect operation of the protection scheme. By employing the proposed protection scheme, fault detection and isolation with a sampling frequency of 8000 Hz is achieved in less than 0.2 ms. A protection scheme should be able to disconnect the faulted section even if one of the main protection units fails; hence, by defining different protection zones for each protection unit, backup protection is realized. Eventually, to show significance of the proposed protection scheme, several case studies are investigated and results are compared with earlier studies.